2021
DOI: 10.31610/trudyzin/2021.325.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the fishes of the Severnaya Zemlya archipelago and the spawning area of polar cod Boreogadus saida (Gadidae)

Abstract: Data on the fishes of the high-latitude Severnaya Zemlya archipelago (the North Land) is presented. The archipelago is located in the Arctic on the border between the Kara Sea and the Laptev Sea. The ichthyofauna of the archipelago has not been studied; therefore, even small collections are of interest. Fish samples were obtained during the expedition “Open Ocean: Arctic Archipelagos – 2019: Severnaya Zemlya”. In addition, the samples from this area in the collections of the Zoological Institute (ZIN) were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In Greenland waters, gelatinous snailfish was recorded at depths of 5-1460 m (Møller et al, 2010). It was caught in coastal waters of the Severnaya Zemlya archipelago by divers at depths of 7-20 m (Chernova et al, 2021). Reports on the finding of gelatinous snailfish at a depth of 1880 m (Kirillov et al, 2016) are doubtful, since it is suggested that it was caught in the pelagic zone above the indicated depth (Able, 1990;Mecklenburg et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greenland waters, gelatinous snailfish was recorded at depths of 5-1460 m (Møller et al, 2010). It was caught in coastal waters of the Severnaya Zemlya archipelago by divers at depths of 7-20 m (Chernova et al, 2021). Reports on the finding of gelatinous snailfish at a depth of 1880 m (Kirillov et al, 2016) are doubtful, since it is suggested that it was caught in the pelagic zone above the indicated depth (Able, 1990;Mecklenburg et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Liparis tunicatus is the most shallow-water species of the genus in the Arctic seas. It is found almost from the surface, 0 m (Møller et al, 2010) and shallow waters, 7-13 m (Chernova et al, 2021) to a depth of 620 m (Coad and Reist, 2004), but it rarely occurs deeper than 150 m (Parin et al, 2014). In the Laptev Sea and the East Siberian Sea, it was recorded in the depth ranges of 10-94 and 12-54 m, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These results corroborate previous studies conducted on smaller sets of nuclear as well as mitochondrial markers, showing low levels of spatial population structure among polar cod sampled at a relatively large spatial scale 28,36 as well as in the Barents Sea and Arctic Ocean region 26,29 . Based on two hypothesized spawning grounds in the Barents Sea, i.e., in the northwestern Barents Sea and southeastern Barents Sea area [23][24][25] , our findings suggest that natal homing behavior is unlikely to be prominent, and rather indicates that there is high connectivity between different locations and/or sub-populations within the Barents Sea area.…”
Section: Genome-wide Population Structure and Genetic Diversitymentioning
confidence: 91%
“…Despite its central role in the ecosystem, linking higher and lower trophic levels [21][22][23] , in-depth knowledge of its biology, migratory behavior, population structuring, and genomic composition in general is limited. For the Barents Sea area, previous studies have suggested that there are likely two spawning grounds, one in the Northwest of the Barents Sea and one in the southeast Barents Sea, adjacent to Novaya Zemlya [23][24][25] , Russia, suggesting that there could be at least two or more sub-populations within this region. Several studies have been carried out to characterize the population structure of polar cod throughout their circumpolar occurrence, most of which have utilized only a handful to hundreds of genetic markers, and the results have been inconsistent [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%